Human 28S ribosomal RNA sequence heterogeneity. - Gonzalez, I L (1988)
DNA sequencing of several cloned human 28S ribosomal RNA gene fragments has revealed sequence heterogeneity (1) but it was not clear whether these are inactive pseudogenes or are active genes that are transcribed and represented in ribosomes. S1 nuclease analysis allowed us to examine the population of ribosomal RNA molecules of a cell, and we found that 28S rRNA is a heterogeneous assortment of molecules in both mono- and polysomal preparations. Sequence variation, although largely concentrated in variable regions of the molecule, apparently also occurs in the conserved regions.